2020
DOI: 10.1177/1527002520944452
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of National Anthem Protests on National Football League Television Ratings

Abstract: The National Football League’s (NFL) television ratings decreased by approximately 8% during the 2016 season, then a further 10% the following season. These declines coincided with league-wide national anthem protests initiated by Colin Kaepernick at the beginning of the 2016 season. Existing research identifies many determinants of demand for sporting events, but athletes’ protests are seldom considered. We use detailed data on players’ protests and television ratings to construct a new, game-level panel for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Brown and Sheridan (2020) improve upon Watanabe and Cunningham (2020) in some respects. They use game-level data across a four-year period (spanning the 2014 through 2017 regular NFL seasons) to assess the effects of anthem protests on NFL demand.…”
Section: Literature Reviewmentioning
confidence: 87%
See 2 more Smart Citations
“…Brown and Sheridan (2020) improve upon Watanabe and Cunningham (2020) in some respects. They use game-level data across a four-year period (spanning the 2014 through 2017 regular NFL seasons) to assess the effects of anthem protests on NFL demand.…”
Section: Literature Reviewmentioning
confidence: 87%
“…This analysis seeks to build upon Watanabe and Cunningham (2020) and Brown and Sheridan (2020) by developing more precise measures of political ideology tailored to the specific NFL markets and reconsideration of the outcome measure (i.e., TV game ratings). Further, we place greater weight on the effect of past protests on current viewership.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Brown and Sheridan (2020) analyzed NFL television ratings from 2014 to 2018 and found that they significantly declined during the 2016-17 season after the protest began and during the 2017-18 season after Donald Trump publicly criticized protesting NFL players. Some people also expressed anger and frustration toward the protest on social media using the hashtag #boycottNFL (Yoo et al, 2018).…”
Section: Athlete Activismmentioning
confidence: 99%
“… 2 A few studies have analyzed the BLM movement in other contexts, such as the demand for National Football League games (Brown & Sheridan, 2020 ) or lethal use of force by the police (Campbell, 2021 ). …”
mentioning
confidence: 99%